2021
DOI: 10.3390/fermentation7010033
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides Production by Cultivating a Bacterial Isolate from the Hypersaline Environment of Salar de Uyuni (Bolivia) in Pretreatment Liquids of Steam-Exploded Quinoa Stalks and Enzymatic Hydrolysates of Curupaú Sawdust

Abstract: The halotolerant bacterial strain BU-4, isolated from a hypersaline environment, was identified as an exopolysaccharide (EPS) producer. Pretreatment liquids of steam-exploded quinoa stalks and enzymatic hydrolysates of Curupaú sawdust were evaluated as carbon sources for EPS production with the BU-4 strain, and the produced EPS was characterized using FTIR, TGA, and SEM. Cultivation was performed at 30 °C for 48 h, and the cells were separated from the culture broth by centrifugation. EPS was isolated from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 63 publications
(87 reference statements)
4
12
0
Order By: Relevance
“…Images taken at different magnifications confirmed the film-like pattern of the obtained product. The continuous and glittering surface and the compact structure observed have a similar appearance as that of other previously described microbial biofilms [31,32], and it is different from the rather grainy and discontinuous texture revealed by SMS imaging of non-film forming biopolymers [29].…”
Section: Characterization Of the Biofilm 331 Semsupporting
confidence: 46%
See 1 more Smart Citation
“…Images taken at different magnifications confirmed the film-like pattern of the obtained product. The continuous and glittering surface and the compact structure observed have a similar appearance as that of other previously described microbial biofilms [31,32], and it is different from the rather grainy and discontinuous texture revealed by SMS imaging of non-film forming biopolymers [29].…”
Section: Characterization Of the Biofilm 331 Semsupporting
confidence: 46%
“…Based on previously used methodologies [29], the culture broth was centrifuged at 3000 g for 15 min at 4 • C, the cell pellet was discarded, and the cell-free supernatant was treated with ethanol for biofilm precipitation. Three volumes of 99.5% ethanol were added to the supernatant, and the mixture was stored overnight at 4 • C in bottles to allow precipitation of the extracellular polymer.…”
Section: Biofilm Separation and Purificationmentioning
confidence: 99%
“…All extracted FucoPol samples displayed similar TGA curves, with two main degradation steps ( Figure 5 ). The first degradation step, corresponding to weight losses of 8–12%, occurred between around 36 and 137 °C and is related to the elimination of water molecules physically entrapped or/and adsorbed to the polysaccharide through hydrogen bonding [ 45 , 46 ]. Samples F-1 100 and F-1 30 had the lowest weight loss values at this temperature range (10 and 8%, respectively), suggesting they had lower contents of adsorbed water compared to the samples obtained by Methods 2 and 3 that displayed the same weight loss (12%).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we reported an EPS-producing halotolerant bacterial strain isolated from Salar de Uyuni, which is a salt desert at 3600 m a.s.l. in the Altiplano [13]. The study provided some initial input, but further efforts were required to clarify the biotechnological potential of the bacterial isolate and to explore application possibilities of the produced EPS.…”
Section: Introductionmentioning
confidence: 99%